The Relation Between Knowledge, Attitude, and Behavior The Usage of Personal Protective Equipment With Accident at Work on Pt. X Project Apartment Bekasi Workers. - Milla Puspa Andini Alydrus (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Based on the research, which conducted by Vondra Anggi Saputro about the application of PPE (personal protective equipment) with an accident at work in 2015 in the Metal Casting Production Work Unit found that there is a significant relation between acknowledging and attitude. The purpose of this research is that knowing the relation between acknowledging, attitude, and the behavior of application PPE (personal protective equipment) with the accident at the project Apartment Bekasi worker. this research is using the observational type, quantitative descriptive research design with cross-sectional oncoming. Data collection technic did by using a questionnaire sheet from a google form. The population is PT X project apartment Bekasi workers around 150 people. Sample determination in this research is using nonprobability sampling with the purposive sampling method. The result of this research shows the knowledge variable of PPE (personal protective equipment) (P=0,051), attitude variable of PPE (personal protective equipment) (P=0,070), behavior variable of PPE (personal protective equipment) (P=0,674). The three variables represent that there is no significant relation with the accident at work. From the result of this research, there is a significant difference between previous research and this study, due to differences such as statistical tests, the methods used, and other supporting factors.